From Gondwana to GAARlandia: Evolutionary history and biogeography of ogre‐faced spiders (Deinopis). (25th September 2018) - Chamberland, Lisa; McHugh, Anne; Kechejian, Sarah; Binford, Greta J.; Bond, Jason E.; Coddington, Jonathan; Dolman, Gaynor; Hamilton, Chris A.; Harvey, Mark S.; Kuntner, Matjaž; Agnarsson, Ingi
Abstract: Aim: We explore the evolutionary history of the ogre‐faced spiders ( Deinopis ) from their Early Cretaceous origins to present day. Specifically, we investigate how vicariance and dispersal have shaped distribution patterns of this lineage. Within the Caribbean, we test the role of GAARlandia, a hypothesized land bridge that connected South America to the Greater Antilles during the Eocene–Oligocene transition ( 35–33 Ma), in the biogeography of Deinopis . Taxon: Araneae: Deinopidae: Deinopis . Location: Caribbean islands, with additional global exemplars. Methods: Combining standard Sanger sequence data with an Anchored Hybrid Enrichment (AHE) phylogenomic dataset, we use Bayesian inference to estimate the phylogenetic relationships of Deinopis . "BioGeoBEARS" is used to test the GAARlandia hypothesis, and to pinpoint major dispersal events in the biogeographic history of Deinopis . Results: The phylogeny supports the nesting of a Caribbean clade within a continental grade. Model comparisons indicate GAARlandia as the best fitting model, and the biogeographic analyses reflect the geologic history within the Caribbean. Ancient and recent overwater dispersal events are also indicated within this lineage. There is also an ancient 113 Ma split into Old and New World clades. Main Conclusions: The Deinopis phylogeny corresponds well with geography. This is reflected in the support for the GAARlandia land bridge hypothesis and the phylogenetic relationships within and among Caribbean islands mirroring nuances of Caribbean geologic history. Overwater dispersal also plays an important role in the biogeographic history of this lineage as implicated in the colonization of the volcanic and sedimentary Lesser Antilles and in a "reverse" colonization of North America. The spider family Deinopidae is an ancient lineage with origins dating back to Gondwana. While overwater dispersal has clearly played a role in the biogeography of the genus, the Deinopis phylogeny bears a strong signature of ancient geological events.